Binary Toxin Expression by Clostridioides difficile Is Associated With Worse Disease. (10th January 2022) - Young, Mary K; Leslie, Jhansi L; Madden, Gregory R; Lyerly, David M; Carman, Robert J; Lyerly, Matthew W; Stewart, David B; Abhyankar, Mayuresh M; Petri, William A
Abstract: Background: The incidence of Clostridioides difficile infection (CDI) has increased over the past 2 decades and is considered an urgent threat by the Centers for Disease Control and Prevention. Hypervirulent strains such as ribotype 027, which possess genes for the additional toxin C. difficile binary toxin (CDT), are contributing to increased morbidity and mortality. Methods: We retrospectively tested stool from 215 CDI patients for CDT by enzyme-linked immunosorbent assay (ELISA). Stratifying patients by CDT status, we assessed if disease severity and clinical outcomes correlated with CDT positivity. Additionally, we completed quantitative PCR (PCR) DNA extracted from patient stool to detect cdtB gene. Lastly, we performed 16 S rRNA gene sequencing to examine if CDT-positive samples had an altered fecal microbiota. Results: We found that patients with CdtB, the pore-forming component of CDT, detected in their stool by ELISA, were more likely to have severe disease with higher 90-day mortality. CDT-positive patients also had higher C. difficile bacterial burden and white blood cell counts. There was no significant difference in gut microbiome diversity between CDT-positive and -negative patients. Conclusions: Patients with fecal samples that were positive for CDT had increased disease severity and worse clinical outcomes. Utilization of PCR and testing for C. difficile toxins A and B may not reveal the entire picture when diagnosing CDI; detection of CDT-expressing strains is valuable in identifying patients at risk of more severe disease.